ANALYSIS OF THE INFLUENCE OF BRAND AWARENESS, FEATURES AND CONTENT CREATORS IN THE EFOOTBALL GAME ON PLAYERS' DECISIONS TO TOP UP - Wahyu Karobby; Mochamad Rizal Yulianto; Istian Kriya Almanfaluti; Bayu Hari Prasojo (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to examine the effect of brand awareness, game features, and content creators on players’ top-up decisions in the eFootball game. Method: A quantitative research approach was employed, utilizing questionnaires distributed to 96 Generation Z respondents. The collected data were analyzed using multiple linear regression with SPSS software to determine the influence of each variable on players’ purchasing decisions. Results: The analysis revealed that brand awareness and content creators have a significant positive effect on players’ top-up decisions, while game features do not show a significant influence. These results suggest that social and psychological factors related to brand perception and influencer engagement play a stronger role in shaping players’ spending behavior than in-game functionality. Novelty: This study contributes to the growing literature on digital consumer behavior by highlighting the pivotal role of content creators and brand identity in influencing virtual purchasing decisions among Generation Z gamers in the context of eFootball.